Foot Pad Health as Part of On-Farm-Monitoring in Turkey Flocks - Toppel, Kathrin; Spindler, Birgit; Kaufmann, Falko; Gauly, Matthias; Kemper, Nicole; Andersson, Robby (Frontiers in Veterinary Science, 2019)
Currently, there is no consistent approach to on-farm and post-mortem foot pad (FP) assess-ment in turkey husbandry regarding sampling of both feet, sample size of birds and scoring scheme during the production period. Therefore, in a field study, 11,400 turkeys, i.e. 22,800 feet, were macroscopically scored at four-week intervals, 60 birds per flock per date, in ac-cordance with the scale system of Hocking et al. (2008). Spearman’s rho was calculated be-tween the foot pad dermatitis (FPD) score of both feet of an individual. Sample size for FPD monitoring was calculated for several flock sizes, considering expected FPD prevalence, error and confidence level (α=0.01, 0.05, 0.1). To compare macroscopic to histological findings, ten excised FP were histopathologically investigated by hematoxylin & eosin staining. To align manual macroscopic FPD evaluation with a technical system, 20 photographic images of FPD were measured using the ImageJ program. The scores of both feet of an individual correlated between r=0.252 and r=1.000. Thus, both feet of a bird should be monitored, while the worse foot should be evaluated. As an exemplary sample size for on-farm FPD assessment, 77 turkey poults were calculated in a flock of 4,000 birds with an expected FPD prevalence of 40 % and α=0.1. The sample size of monitored birds within a flock should differ and depend on flock size and expected FPD prevalence. Histopathological findings showed normal and non-affected structures of a macroscopic Score 0 and a moderate ulcer of the macroscopic Score 1 and Score 2. The applied assessment scheme should distinguish first alterations and scar tissue as separate scores to differentiate the need for management intervention versus the success of management measures that were already implemented. FPD affected areas were given lower Scores and assessed to be healthier when evaluated by an image system compared to manual assessment. Furthermore, with regard to an increase in camera-based assessments, the boundary of the metatarsal pad needs to be clarified. In conclusion, a new scoring system is needed, as the size of the FP cannot be clearly defined and different tissue textures as well as valid sample sizes were not sufficiently considered.